The impact of climate change on surgical care: A systematic review of the bellwether procedures - Elizabeth F Yates; Lotta Velin; Alexandria Cronin; Abbie Naus; Callum Forbes; Alexis N Bowder; Gabrielle Cahill; Charles J Gravereaux; Matthew T Hey; Colby J Hyland; Omnia El Omrani; Hugh Shirley; et al. (Elsevier, 2023)
Background: With efforts underway globally to scale up access to surgical care for the billions who lack it, understanding the impact of climate change on surgical care delivery is critical for clinicians and policymakers. We aimed to assess the current state of knowledge regarding the impact of climate change on the Lancet Commission on Global Surgery Bellwether Procedures: laparotomy, caesarean delivery and treatment of an open fracture. Methods: Adhering to PRISMA guidelines, we performed a systematic review of PubMed, Embase, CINAHL and Web of Science. We included studies that incorporated at least one of each of our two sets of search terms: (1) a specific Bellwether Procedure or its directly related pathophysiology, and (2) a climate change pressure (e.g. extreme heat, major storm, etc.). We excluded studies published before January 1, 2000; in languages outside coauthors' fluency; and those without primary data (e.g. meta-analyses). Two co-authors screened each abstract and then the qualifying full articles for inclusion and data extraction. Our study is registered in PROSPERO (#CRD42021271933). Results: We initially identified 4,618 references, narrowed to 32 for final analysis. Most studies (n = 18, 56.3%) were conducted in high income countries. Only one study was conducted in Africa; none were conducted in South America or the Western Pacific. Caesarean section was the most studied procedure (n = 20, 54.1%) and major storms were the most studied climate change pressure (n = 14, 37.8%). Conclusion: Overall, the impact of climate change on surgery is understudied. Major specific content gaps include laparotomy procedures; long-term climate pressures (e.g. heat, air pollution); geographic regions in South America, the Western Pacific and Africa; and low income country contexts. Though the existing body of literature is small, current trends can inform future research and policy initiatives in global surgery.